Bilateral Pleural Effusions as an Initial Presentation in Primary Sjögren’s Syndrome - Go Makimoto; Michiko Asano; Nobukazu Fujimoto; Yasuko Fuchimoto; Katsuichiro Ono; Shinji Ozaki; Koji Taguchi; Takumi Kishimoto (Case Reports in Rheumatology)
Sjögren’s syndrome (SS) is a systemic autoimmune disease characterized by sicca symptoms. Interstitial pulmonary fibrosis and tracheobronchial sicca are the most common symptoms of pulmonary involvement in primary SjS, and they are rarely accompanied by serositis such as pleuritis or pericarditis. We report a case of SS presenting initially with bilateral pleural effusions. A 63-year old man was admitted to our hospital with a one-month history of cough, dyspnea, and right chest pain. Chest-computed tomography revealed bilateral pleural effusions. Serum anti-SS-A antibody titer was 1 : 256. Ophthalmological examination revealed a positive Schirmer test. Lip biopsy showed atrophy and plasmacytic infiltration of the salivary gland. Corticosteroid treatment was initiated. Pleural effusions were almost completely resolved by day 30. The patient has not experienced any recurrence.